Analysis of Occupational Safety and Health Administration (OSHA) noise standard violations over 50 years: 1972 to 2019. Issue 7 (4th May 2020) - Park, Sungwon; Johnson, Michael D.; Hong, OiSaeng
Abstract: Introduction: Noise exposure has long been an occupational health concern and has been an important area of focus of the Occupational Safety and Health Administration (OSHA) since its founding. Nevertheless, it remains unclear what effects OSHA's noise standards have had on employer efforts to reduce risks. Consequently, a review of OSHA noise standard violations was performed to clarify the violation trends between 1972 and 2019. Methods: Using the OSHA Information System, researchers identified 119 305 violations involving four noise standards between 1972 and 2019: 29 CFR 1910.95, occupational noise exposure in general industry; 1926.52, occupational noise exposure in construction; 1926.101, hearing protection in construction, and 1904.10, recording criteria for cases involving occupational hearing loss. Violation frequencies of noise standard subparagraphs and relationships to factors such as industry differences were analyzed using descriptive statistics and t tests. Results: The most commonly violated noise standard was 1910.95 in manufacturing. Such violations rose between 1972 and 1985 and then declined steadily. Whether in general industry or construction, four noise standards were most‐frequently cited: lack of feasible administrative or engineering controls (1910.95[b] and 1926.52[d]) and inadequate hearing conservation program (1910.95[c] and 1926.52[b]). These violations were more highly penalized (mean = $1036.50) than other subparagraph violations (mean = $915.80). Programmed and unprogrammed inspections generated similar violation quantities except between 1980 and 1985, when programmed inspections exhibited a sharp spike in violations. Conclusion: The study identified trends in OSHA noise standard violations and possible explanations for those trends. The study findings can support development of more practical noise‐exposure protection policy.